PERAN SERTA MASYARAKAT DALAM ADVOKASI TANAH BMN (BARANG MILIK NEGARA) - Heri - Suhardi; Sarip Sarip (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2021)
Utilization is the utilization of State/Regional Property that is not used for carrying out the duties and functions of ministries/institutions/regional work units and/or optimizing State/Regional Property by not changing the ownership status of Regional Property (BMD). The results of the discussion show that the use of BMD for regions to increase their PAD is not carried out according to the applicable mechanism because it is widely misused, especially in the Cirebon City Government with the motive of illegal acts which are indicated as criminal acts with the problem of the State Property Grant (BMN) of former Pertamina assets as as stated in the Decree of the Minister of Finance Number KMK-247/MK.6/2019 dated 24 September 2019 cannot be transferred from the Cirebon City Government to other parties. There are types of utilization of borrow-to-use, BGS/BSG, Lease, Cooperation in Utilization that can be carried out in the form of non-infrastructure utilization, while in the form of infrastructure, the forms of utilization that can be selected are lease, cooperation in utilization and cooperation in providing infrastructure. Each method of asset utilization (except borrow-to-use) has its own form of contribution that can increase regional income. Based on the facts that the Cirebon City Government and other parties (Gunung Jati Self-Help Education Foundation) deliberately ignore the rules and provisions of the laws and regulations that apply to date and do not carry out the option of using/utilizing BMD related to the lease on the establishment of the campus used by the community. The Faculty of Medicine, Universitas Swadaya Gunung Jati which has been occupied for lectures, on the use of part of the land in the Bima Stadium area is part of the Regional Property belonging to the Regional Government of Cirebon City in the form of land with an area of ??+/- 10,300 m2 which is currently problematic. Keywords: Utilization, BMN/BMD, transferable.